A retrospective study (2013-2019) in clinical management involving diseases of footrot in small ruminants from selected farms in Klang Valley - Revathi Wardan,
Footrot disease is one of the most common problems in ruminants in Malaysia and it has been classified as one of the most costly disease throughout the world. However, there is a lack of published studies or data pertaining to this topic despite its high incidence particularly in our local setting. In this study, data on common footrot diseases and its clinical signs, common drug usage for treatment, and further follow-up plan after first farm visit was tabulated and analyzed and the correlation with the effectiveness and successful rate in curing the disease from the planned treatment was tabulated. From this study, young aged animals that are less than two (2) years old in small ruminant are reported with the bacterium infection. Thus, majority footrot diseases are clinically managed with proper diagnosis and treated with Oxytetracycline as preferred antibiotics and Flunixin Meglumine as anti- inflammatory drug of choice. It is found that not many footrot diseases cases were revisited after the first farm visit In conclusion, from this study the data on common footrot diseases and its clinical signs, common drug usage for treatment, and further follow-up plan after first farm visit were identified and this will give additional information's and will assist field veterinarians on clinical management in small ruminant livestock in our local settings and also to understand the necessity in the compliance of the veterinarians/clinicians in updating the clinical cases by constant follow up via farm revisits.